Strategy to Increase Market Share of Bank Syariah Indonesia (BSI) in North Sumatra Region - Annisa Prastiwi; Andri Soemitra; Ahmad Amin Dalimunte (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study aims to find out how the top priority strategy for increasing BSI market share in North Sumatra by presenting internal and external conditions that have been carried out and discussed with experts. Then as an alternative to additional policies, the researcher also explained some of the urgency of handling that needs to be applied so that market share development can be directed. The method used is a SWOT analysis. there were seven respondents who filled out their respective questionnaires. Based on the results of the SWOT analysis, the quadrant of strategies obtained after being processed in the IFAS and EFAS matrices is a defensive strategy. This strategy means that it is necessary to minimize weaknesses and avoid threats. The results obtained from the SWOT analysis can be read with a SWOT quadrant that shows the Diversification strategy contained in the ST (Strength – Threat) strategy